Medical Malpractice A Physician$1 (Bs Sourcebook /s - Anderson, Richard E.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
What is behind the medical malpractice crisis? What legal reforms would alleviate the crisis? What can you do to prevent litigation? What do you do when you have been sued? Are there alternatives to the current system? How does the medical malpractice insurance industry function? In Medical Malpractice: A Physician's Sourcebook, a panel of physicians, attorneys, academics, researchers, and insurance industry experts consider these and other questions about the origin, nature, and ramifications of the medical malpractice litigation crisis, as well as possible solutions and alternatives to the current system. The authors focus on the clinical face of litigation from the perspective of the practicing physician in a variety of specialties, ranging from family and emergency medicine to anesthesiology, obstetrics, gynecology, and plastic surgery. Special consideration is given to breast cancer and Pap smear litigation, risk management for the family physician, and the importance of effective patient communication. Additional legal chapters examine the litigation process itself, offering insight into winning medical malpractice lawsuits, the role of the physician as expert witness or defendant, the process of discovery and deposition, and how a plaintiff's attorney views risk reduction. Public policy experts argue the case for legal reform, suggest changes in medical-legal jurisprudence that can be of immediate benefit, and reflect on the broader problems of our entire health care system and its interface with law and social policy. Authoritative and wide-ranging, Medical Malpractice: A Physician's Sourcebook gets to the heart of issues facing physicians and surgeons today. It focuses on the practical aspects of medical malpractice lawsuits, and prepares physicians and surgeons to participate in the public policy debate by addressing current topics that will help them understand the crisis, the threat to healthcare access, and the possibilities for legal reform.
Insurance -- Insuring the Practice of Medicine -- Legal -- What Every Doctor Should Know About Litigation -- Risk Reduction From a Plaintiff Attorney$1 (Bs Perspective -- The Physician As a Witness -- The Judicial Process -- The Clinical Face of Litigation -- Communication and Patient Safety -- E-Medicine in the Physician$1 (Bs Office -- Risk Management for the Family Physician -- Emergency Medicine -- Anesthesiology -- Malpractice and Medical Practice -- Breast Cancer Litigation -- Pap Smear Litigation -- Medical Liability in Plastic and Reconstructive Surgery -- Legal Reform and Health Care -- The Case for Legal Reform -- Health Policy Review -- New Directions in Medical Liability Reform.s
Keywords: Medicine; Internal medicine; Medicine & Public Health; Internal Medicine; Electronic books